In Vivo hip joint loading during cross-country skiing on a simulator - Aschenbrenner, Daniela; Scupin, Pamela; Dymke, Jörn; Zhou, Sijia; Maleitzke, Tazio; Hainzl, Stefan; Duda, Georg N.; Perka, Carsten; Wolfarth, Bernd; Winkler, Tobias; Damm, Philipp (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundReturn to sports following total hip arthroplasty (THA) is important to an increasingly younger and active clientele. However, knowledge about in vivo joint forces during sports is scarce and often only estimated. As skiing is controversially debated as an activity following THA, we measured in vivo joint loads in instrumented THAs during cross-country ski simulation.MethodsFive untrained subjects who had previously received instrumented THAs were instructed to perform double poling and diagonal poling exercises on a ski simulator and to walk on a treadmill at 4 km/h as a reference exercise. The joint contact force, bending moment, and torsion torque on the implant were determined. Time-load patterns were generated. Loading peaks were compared intra-and inter-individually to walking. Statistical parameter mapping was used to visualise significant differences between exercises across the movement cycle.ResultsLoading maxima were mostly lower or adjacent to loading maxima of walking, except for diagonal poling with foot lift. Differences in execution of double poling resulted in different time-load patterns of torsion torque. Diagonal bending moments exceeded walking bending moments slightly. Outliers were observed.ConclusionDouble or diagonal poling can be safely practiced by THA patients on a ski simulator in the late postoperative period due to mostly lower or adjacent loading forces to walking. Unilateral standing phases should be minimized. Patient’s experience and bone quality affect recommendation of this sport. Limitations concern limited generalizability of small cohort and simulated environment.